2019
DOI: 10.1101/798033
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Reduced Hippocampal and Amygdala Volumes as Mechanisms of Stress Sensitization to Depression following Childhood Violence Exposure

Abstract: OBJECTIVE:Stressful life events are more likely to trigger depression among individuals exposed to childhood adversity. However, the mechanisms underlying this stress sensitization remain largely unknown. Any such mechanism must be altered by childhood adversity and interact with recent stressful life events, magnifying their association with depression. This study investigated whether reduced hippocampal and amygdala volumes are mechanisms of stress sensitization following childhood violence exposure. METHODS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 34 publications
(50 reference statements)
0
3
0
Order By: Relevance
“…For instance, Black youth in the highest-structural stigma states had a hippocampus that was 177 mm 3 smaller than those in the lowest-structural stigma states, equivalent to about 2.3% of the average hippocampal volume among Black youth in the ABCD sample. A recent study, by comparison, found that the reduction in hippocampal volume attributable to childhood experiences of interpersonal violence was 364 mm 3 (64), about 3.8% of the average volume in that sample. To further contextualize this finding, the magnitude of the observed difference in hippocampal size between high and low structural stigma states was equivalent to the predicted impact of a $20,000 difference in annual family income in this sample.…”
Section: Discussionmentioning
confidence: 92%
“…For instance, Black youth in the highest-structural stigma states had a hippocampus that was 177 mm 3 smaller than those in the lowest-structural stigma states, equivalent to about 2.3% of the average hippocampal volume among Black youth in the ABCD sample. A recent study, by comparison, found that the reduction in hippocampal volume attributable to childhood experiences of interpersonal violence was 364 mm 3 (64), about 3.8% of the average volume in that sample. To further contextualize this finding, the magnitude of the observed difference in hippocampal size between high and low structural stigma states was equivalent to the predicted impact of a $20,000 difference in annual family income in this sample.…”
Section: Discussionmentioning
confidence: 92%
“…The metaanalysis included different types of social stressors, some of which are not relevant to urban social risk (e.g., childhood trauma), but is nevertheless informative on the key role for the amygdala in the neural effects of the social environment. Finally, recent evidence linked psychosocial stressors (childhood adversity, migration and urban living) in healthy volunteers to reduced volume of the amygdala (Weissman et al, 2019) and increased connectivity between striatal and cortical regions involved in salience and reward processing (McCutcheon et al, 2019). Interestingly, recent evidence from the animal literature shows that repeated social defeat is associated with sensitized neurons and microglia over several weeks (Weber et al, 2019).…”
Section: Risk Attributes Of the Urban Environment And The Brainmentioning
confidence: 99%
“…In addition, evidence from the animal literature shows that repeated social defeat is associated with sensitized neurons and microglia over several weeks (Weber et al, 2019). Such changes at cell level might drive higher-level changes in brain structure, and could contribute to various mental health conditions that have been associated with stress sensitization and reward processing deficits (Gerin, Hanson, Viding, & McCrory, 2019; Weissman et al, 2019; Whitton, Treadway, & Pizzagalli, 2015).…”
Section: Introductionmentioning
confidence: 99%